2021
DOI: 10.31101/jhtam.2093
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the failure of exclusive breastfeeding practice: a scoping review

Abstract: Background:  In some countries, exclusive breastfeeding is practiced in a limited number of cases and for a short period of time; on an international scale in 2012, only 39% of six-month-old babies were exclusively breastfed. This breastfeeding rate falls short of the World Health Organization's recommended threshold (WHO). According to WHO, to reach the global level by 2025, which is 50% of mothers must exclusively breastfeed for 6 months after giving birth, a strategy must be developed to encourage and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study emphasized the impact of variables such as lack of maternal knowledge, nipple and breast tenderness, low milk supply, maternal attitude, and lack of confidence. Further research conducted by Sulasmi et al (2021) revealed that variables such as the number of previous pregnancies, regular visits to healthcare providers during pregnancy, maternal age, family support, families with limited financial resources, and living in rural areas are key factors influencing exclusive breastfeeding practices in Indonesia (Gayatri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study emphasized the impact of variables such as lack of maternal knowledge, nipple and breast tenderness, low milk supply, maternal attitude, and lack of confidence. Further research conducted by Sulasmi et al (2021) revealed that variables such as the number of previous pregnancies, regular visits to healthcare providers during pregnancy, maternal age, family support, families with limited financial resources, and living in rural areas are key factors influencing exclusive breastfeeding practices in Indonesia (Gayatri, 2021).…”
Section: Introductionmentioning
confidence: 99%